The ‘Kalamata 1821: Roads of Freedom’ : Project: Technological and Management Advances for Cultural Heritage - Zacharias , Nikolaos; Panagiotidis , Vayia; Valantou , Vasiliki; Rigas , Georgios (Technical Annals, 2022)
The purpose of this paper is to offer an overview of the Cultural Heritage Enhancement project “Kalamata 1821: Roads of Freedom” after its completion. “Kalamata 1821: Roads of Freedom” has been a co-financed by Greece and the European Union project which was placed under the wider scheme “Research, Creation and Innovation” NSRF (ESPA) 2014-2020. The pro-ject was implemented during the 2018-2021 period, i.e. by taking advantage of the celebration of the landmark of two centuries (1821-2021) since the uprising which led to the establishment of the Greek State. It was executed via a tripartite research association which consisted of the University of the Peloponnese, which assumed the role of the coordinator, the Community Enterprise of the Municipal-ity of Kalamata (ΦΑΡΙΣ) and the film production company View Master Films. The project’s aim has been to augment the footprint of Kalamata’s unique mod-ern heritage and make it known and accessible to wider and diversified audiences. The paper outlines the historical background and the conjuncture that inspired the project and thereafter traces the course of its deliverables, namely the produc-tion of the feature-length film “Wind of Freedom 1821”, the “Kalamata 1821 Digital Museum”, and the “Kalamata 1821” brand. It discusses how the pandemic affected the filming of the movie but despite the imposed delay it was fulfilled and screened in Kalamata’s Dance Hall in July 2021. It shows how the “Kalamata 1821 Digital Museum” set an example for raising the awareness of a city’s herit-age via the employment of new technologies. It presents how the “Kalamata 1821” brand attempts to set in motion the various cultural currents of the city in order to blend the historical tradition with the contemporary creativity. Addition-ally, it showcases the most successful aspect of the “Kalamata 1821” brand, i.e. the “Flavours of ‘21” and it discusses the digital applications that were developed but eventually were not used due to the ramification of the pandemic-related re-strictions.